Validation of Probability Equation and Decision Tree in Predicting Subsequent Dengue Hemorrhagic Fever in Adult Dengue Inpatients in Singapore - Thein, Tun L. (The American Society of Tropical Medicine and Hygiene, 2011)
We developed a probability equation and a decision tree from 1,973 predominantly dengue serotype 1 hospitalized adult dengue patients in 2004 to predict progression to dengue hemorrhagic fever (DHF), applied in our clinic since March 2007. The parameters predicting DHF were clinical bleeding, high serum urea, low serum protein, and low lymphocyte proportion. This study validated these in a predominantly dengue serotype 2 cohort in 2007. The 1,017 adult dengue patients admitted to Tan Tock Seng Hospital, Singapore had a median age of 35 years. Of 933 patients without DHF on admission, 131 progressed to DHF. The probability equation predicted DHF with a sensitivity (Sn) of 94%, specificity (Sp) 17%, positive predictive value (PPV) 16%, and negative predictive value (NPV) 94%. The decision tree predicted DHF with a Sn of 99%, Sp 12%, PPV 16%, and NPV 99%. Both tools performed well despite a switch in predominant dengue serotypes.